정이와 양시, 『西銘』을 논하다 - 정환희(Jeong, Hwan-Hui) (人文學硏究, 28(0), 2017)
『龜山集』에는 정이와 양시 사이에 교환된 서신이 보존되어 있다. 그 서신 가운데 3통의 편지는 그 둘 사이의『西銘』에 대한 입장차가 드러난다. 첫 번째 서신에서 양시는『西銘』이 도덕적 원리의 보편성만 강조하고, 도덕적 행위의 비근성과 특수성은 도외시했다고 본다. 이에 대해 정이는 두 번째 서신에서 리일분수(理一分殊) 개념을 창안하면서, 양시의『西銘』이해가 적절치 않다고 주장한다. 이러한 정이의 입장을 양시는 제대로 이해하지 못했고, 세 번째 서신에서 양시는 자신의 입장을 고수한다. 연구자가 볼 때, 정이와 양시의『西銘』논의는 분명 리일분수라는 독창적인 개념어를 남겼지만,『西銘』토론 측면에서 볼 때 양자의 토론은 생산적이지 못했다. In the work Guishanji(龜山集), there are letters exchanged between ChengI(程頤) and YangShi (楊時). Among the letters, three specific letters reveal the position of XiMing(西銘) within communication between the two. In the first epistle, YangShi notes that XiMing emphasizes the universality of moral principles and neglects the inadequacy of moral conduct. In response to this, in the second epistle, ChengI claims that Yangshi’s an understanding of Ximing is not appropriate, by inventing the concept of Liyifenshou(理一分殊). Yangshi did not fully understand Chengi’s perspective, and in the third epistle, he defends his position. As researchers believe, their discussion obviously left behind the unique concept of the Liyifenshou. But in terms of the Ximing debate, the discussions on both sides were not productive. KCI Citation Count: 3